1983
DOI: 10.1128/iai.41.2.523-526.1983
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antigenically distinct rotaviruses from infants

Abstract: Antigenically distinct rotaviruses, i.e., viruses morphologically identical to conventional rotaviruses by electron microscopy, yet lacking the common group antigen(s) detected by an enzyme-linked immunosorbent assay, were found in 2 of 51 fecal samples from Bulgarian infants with rotavirus gastroenteritis. These antigenically distinct viruses contained 11 segments of double-stranded RNA, but they demonstrated a unique RNA migration profile after electrophoresis of the genome RNA in polyacrylamide gels. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…Recently, several viral agents have been reported to be the causative agent of diarrhea outbreaks, including group B rotaviruses found to be responsible for several large outbreaks in China [Hung et al, 1983[Hung et al, , 1984Chen et al, 19851. In Japan, small round viruses are identified most frequently as a causative agent of diarrhea outbreaks Sekine et al, 19891. On the other hand, group C rotaviruses are known as causative agents of gastroenteritis in bovine species [Saif et al, 19801, but only a few sporadic cases have been attributed to this virus in humans [Dimitrov et al, 1983;Espejio et al, 1984;Ohseto, 19901. Our data, how- ever, suggest that group C rotaviruses may play an important role in outbreaks of viral diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several viral agents have been reported to be the causative agent of diarrhea outbreaks, including group B rotaviruses found to be responsible for several large outbreaks in China [Hung et al, 1983[Hung et al, , 1984Chen et al, 19851. In Japan, small round viruses are identified most frequently as a causative agent of diarrhea outbreaks Sekine et al, 19891. On the other hand, group C rotaviruses are known as causative agents of gastroenteritis in bovine species [Saif et al, 19801, but only a few sporadic cases have been attributed to this virus in humans [Dimitrov et al, 1983;Espejio et al, 1984;Ohseto, 19901. Our data, how- ever, suggest that group C rotaviruses may play an important role in outbreaks of viral diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…rotaviruses are classified as group A and atypical rotaviruses as groups B-G [Saif, 19901. Group C rotaviruses were first identified as a causal agent of gastroenteritis in swine in 1980 [Saif et al, 19801 and in humans in 1982 [Rodger et al, 19821. Human group C rotavirus infections, however, have been reported only occasionally in many countries [Dimitrov et al, 1983;Espejio et al, 19833, including Japan, where only a few outbreaks have been reported [Matsumoto et al, 1989;Ohseto, 19901. Group A rotaviruses as well as porcine [Saif et al, 19881 and bovine [Tsunemitsu et al, 19911 group C rotaviruses can be propagated serially in cell cultures. However, attempts to propagate other group C rotaviruses or other atypical rotaviruses have failed.…”
Section: Introductionmentioning
confidence: 99%
“…Large outbreaks of severe 0 1994 WILEY-LISS, INC. diarrhea in adults have been associated with Group B rotaviruses in several provinces of China [Hung et al, 19841, but not elsewhere. The Group C rotaviruses have been associated with either sporadic diarrheal illness or small outbreaks of diarrhea in infants and children in several different countries throughout the world [Beards et al, 1989;Bonsdorf and Svensson, 1988;Bridger et al, 1986;Brown et al, 1988;Caul et al, 1990;Chen et al, 1988;Dimitrov et al, 1983;Espejo et al, 1984;Matsumota et al, 1989;Nicholas et al, 1983;Penaranda et al, 1989;Rodger et al, 1982;Saif and Theil, 19851. Group C rotaviruses were isolated initially from diarrheic piglets in the United States [Saif et al, 19801, and limited surveys suggest this virus commonly infects pigs in North America, Europe, and Australia [Bohl et al, 1982;Nagesha et al, 1988;Saif, 1990;Saif and Theil, 19851.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently it was believed that all rotaviruses possessed a common group antigen sited o n the inner capsid w o o d e et at, 19761. However, numerous rotavirus strains have more recently been discovered that are quite antigenically distinct from the rotaviruses with the conimon group antigen and have been found mainly in pigs, cows, lambs, rats, birds [Saif et al, 1980;Bohl et al, 1982;Snodgrass et al, 1984;McNulty et al, 19811, and, to a very small extent until recently, in human beings [Rodger et al, 1982;Nicolas et al, 1983;Dimitrov et al, 1983; Espejo et al, 19841. The earlier conventional rotaviruses with the common group antigen are now placed in serogroup A, and (by analogy with influenza) the more recently discovered rotaviruses, which are serologically completely different from them, are placed in groups B, C, D, etc [Pedley et al, 19831.…”
Section: Introductionmentioning
confidence: 99%